Multimodal implementation of clinical practice guidelines on bronchiolitis: Ending the overuse of diagnostic resources - Ana Isabel Maraña Pérez; Juan Manuel Rius Peris; Cristina Rivas Juesas; Javier Torrecilla Cañas; Sara Hernández Muelas; Alberto de la Osa Langreo (Elsevier, 2018)
Introduction: Clinical practice guidelines have been shown to be valuable tools for guiding medical decisions. However, their mere publication has not reduced the variability of practice in terms of the way acute bronchiolitis is managed. Method: A before-and-after study design was used to analyse the effectiveness of a method of disseminating diagnostic recommendations among physicians regarding the management of infants, hospitalised due to bronchiolitis. Patients with comorbidities, ex-premature patients, and patients transferred to other hospitals were excluded. The diagnostic resources studied were: chest X-ray, full blood count, C-reactive protein, blood culture, venous blood gas, and determination of the respiratory syncytial virus. Eleven epidemic periods were analysed. Results: A total of 259 patients were studied including 98 in the pre-intervention group (2006-2010), and 131 in the post-intervention group (2011-2017). The intervention took place in October of 2010 and 2011. A comparison of the two periods showed that the use of chest X-rays dropped from 73.5% to 16% (P < .01), full blood counts from 51% to 21.4% (P < .01), C-reactive protein from 48% to 22.1% (P < .01), and blood cultures from 23.5% to 7.6% (P < .01). Length of stay dropped by 0.6 (SD = 1) days and there were no differences in re-admission rates. Conclusions: The organised and systematised dissemination, using a multimodal method, of the diagnostic recommendations contained in the clinical practice guidelines on bronchiolitis, is capable of transforming the clinical practice by reducing the use of diagnostic resources, without an increase in the re-admission rate. Resumen: Introducción: Las Guías de Práctica Clínica han demostrado ser herramientas valiosas para orientar las decisiones de los médicos. Su mera publicación no ha reducido la variabilidad en el manejo de la bronquiolitis aguda, y se siguen utilizando de forma excesiva determinados recursos para su atención. Método: Mediante una investigación con un diseño antes-después, se estudió la efectividad de un método de difusión de recomendaciones diagnósticas para el manejo de lactantes hospitalizados por bronquiolitis. Pacientes con comorbilidades, exprematuros y los que fueron trasladados a otros centros sanitarios fueron excluidos. Los recursos diagnósticos estudiados fueron: radiografía de tórax, hemograma, proteína C reactiva, hemocultivo, gasometría venosa y determinación de virus respiratorio sincitial. Se analizaron un total de 11 temporadas epidémicas. Resultados: Se estudiaron 259 pacientes, 98 en el periodo preintervención (2006-10) y 131 en el posintervención (2011-17). La intervención se llevó a cabo en octubre de 2010 y 2011. Comparando los dos periodos, disminuyó el uso de radiografía de tórax, 73,5 a 16% (p < 0,01); hemograma 51 a 21,4% (p < 0,01), PCR 48 a 22,1% (p < 0,01) y hemocultivo 23,5 a 7,6% (p < 0,01). La duración de la hospitalización disminuyó 0,6 (DE = 1) días y no hubo diferencias en los reingresos. Conclusiones: La difusión organizada y sistematizada, mediante un método multimodal, de las recomendaciones diagnósticas contenidas en una guía de práctica clínica sobre bronquiolitis, es capaz de transformar la práctica médica, reduciendo el uso de recursos diagnósticos, sin incrementarse los reingresos.